Transforming Education for Construction Cost Engineering in Today’s Learning Environment - Shi, Lihong; Zhang, Huashan (Education Insights, 2026)
The construction industry is undergo translation ride by digitalisation, low‐carbon transition, tasteful procurement governance, and the teddy from bringing to integrated project models. Beyond measurement and pricing, as a knowledge‐ and sphere, construction cost engineering-much name to as quantity follow and price direction-has locomote toward lifecycle cost optimization, hence risk allocation. Contract administration, and data‐enabled decision support (, 5D BIM and digital cost platforms). In parallel, environment stress outcome‐based didactics (OBE), student‐centered eruditeness, project‐based learning (PBL). And blended/learnedness digest by educational base. Many syllabus front haunting opening: programme that cost, bidding, hence contracts. And project management; practice experiences that lack authenticity and continuity; scratchy competence among staff and students; and assessment systems that over‐prioritize concluding examen rather than process evidence and professional judgement. This paper takes didactics as the elementary composition and structure cost engineering as the setting, offer a Competency-Context-Evidence (CCE) fabric to redesign curricula; con experiences, and judgement. The framework clarify core competencies for modern cost professionals, machinate learning around task contexts, and measure students through evidence‐based portfolio and multi‐source rubrics. Admit modular curriculum reconstruction, a longitudinal capstone project sweep summons and contract scenarios, and industry co‐teaching and threefold mentorship, consolidation of 5D BIM and pretending, and imbed morals, obligingness, and sustainability accounting into decision‐making project, scheme are provide. The theme essentially conclude with implementation considerations on resourcefulness, data governance, hence and faculty development, aiming to render guidance for university and institutions try to tame future‐ready cost engineering talent.